Rotter's node metastases. Therapeutic and prognostic considerations in early breast carcinoma. - Cody, H S (1984)
In 500 consecutive modified radical mastectomies (MRM) performed for clinically early (T1 N0) breast carcinomas between 1975 and 1982, the interpectoral lymph nodes (IPN) were separately sampled at the end of the operative procedure. Among the patients consistently sampled (1979-1982), lymph nodes were found in 73%. Interpectoral lymph node metastases were found in 2.6% of all patients, 3% of patients with infiltrating cancers, and 4% of patients sampled. A total of 8.2% of axillary node positive and 0.5% of axillary node negative patients had IPN disease. Among the 13 patients with positive IPN, there were no differences in tumor size or location from the entire group. The two patients whose only nodal metastases were to the IPN are currently disease-free without having received systemic adjuvant therapy. These data suggest that for early breast cancers treated by MRM, routine excision of the IPN is of potential therapeutic or prognostic benefit in very few cases. However, as MRM is increasingly applied to patients with more locally advanced disease (T2-3, N1b-N2), metastases in unexcised IPN may become a more significant source of local or systemic treatment failure.